2018
DOI: 10.1007/s40596-017-0881-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health During Residency Training: Assessing the Barriers to Seeking Care

Abstract: Despite feeling that they require mental health services, few trainees actually sought care. This study identifies an overall need for improved access to mental health providers and psychoeducation for medical housestaff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…However, a 2009 review in the United States of America found that 96% of the state medical licensing board applications reviewed required physician applicants to disclose any personal history of psychiatric illnesses [124] and some of the questions cast physician illnesses ‘in a punitive context’. There have been calls for the disclosure of the history of psychiatric illness to be non-compulsory as this is a barrier to medical students and residents seeking care for their mental health [125,126]. In addition, medical schools can provide confidential access to off-site mental health services for students, as it has been found that medical students desire confidentiality and privacy when seeking medical services [112].…”
Section: Discussionmentioning
confidence: 99%
“…However, a 2009 review in the United States of America found that 96% of the state medical licensing board applications reviewed required physician applicants to disclose any personal history of psychiatric illnesses [124] and some of the questions cast physician illnesses ‘in a punitive context’. There have been calls for the disclosure of the history of psychiatric illness to be non-compulsory as this is a barrier to medical students and residents seeking care for their mental health [125,126]. In addition, medical schools can provide confidential access to off-site mental health services for students, as it has been found that medical students desire confidentiality and privacy when seeking medical services [112].…”
Section: Discussionmentioning
confidence: 99%
“…75 Another study looking at residents found that only 24% of residents who felt they needed mental health care sought treatment. 76 Residents cited lack of time, concern of confidentiality, and cost as barriers to treatment. Encouragingly, studies looking at physicians who participated in either individual or group counseling with a trained professional showed a lasting reduction in EE for up to three years.…”
Section: Validated In Physician Populationsmentioning
confidence: 99%
“…21 These conflicts leave residents hesitant to disclose these issues or to request time off for fear of a lack of confidentiality, stigma, documentation on academic record, and downstream consequences for licensure and employment. [28][29][30][31][32] In addition, many well-meaning wellness initiatives disproportionately focus on individual factors without adequate attention to systematic contributors to burnout, despite research that points to the learning environment as a major driver of resident burnout. [33][34][35]…”
Section: Introductionmentioning
confidence: 99%